Ke arah memperkasakan islamisasi seni muzik sebagai satu alternatif : satu pengamatan awal - Mohamad Kamil Bin Hj Ab Majid,; Muhammed Bin Yusof, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2008)
The interest for music within community especially youth generation has risen up nowadays. This situation is more noticeable with the emergence of reality based entertainment. Even though, it has being argued that the growth of local music industry either traditional or modern has moved from its’ real objectives which are the harmonious and the submission to God. This situation is caused by the affiliation and the clash between the good values and the negative aspects which are existed within the music. With the consequence, this article will discuss music from the Islamic perspective and the opinions of Muslim Scholars. Furthermore, the Islamization concept of music will be introduced as a creative solution and its’ relevance as an alternative entertainment nowadays.